Accelerated Aging of Mungbean Seed for Longevity Evaluation in the Humid Tropics - Wullop Santipracha; Quanchit Santipracha; Chusri Narongrach (Agriculture and Natural Resources, 1993)
Seeds of three mungbean varieties, PSU 1, Uthong 1 and KPS 1 Were accelerated aged in 100% RH at 43, 45 and 47 °C for 48, 72 and 96 hr. Seed quality from each temperature and time of accelerated aging were correlated to the seed stored in paper bags at room temperature for one year to evaluate seed longevity in the humid tropics. Seed accelerated aging could not overcome all of the hard seeds but lower seed viability and vigor. The accelerated aging of mungbean seed for longevity evaluation in the humid tropics in 43 °C for 96 hr in 100% RH.